МАКРОФІНАНСОВА ВІДПОВІДАЛЬНІСТЬ ЦЕНТРОБАНКІВ: ТЕОРЕТИЧНІ ЗАСАДИ ТА ІНСТИТУЦІОНАЛЬНІ ДИЛЕМИ (Світ фінансів, 2017)
Козюк В. В. Макрофінансова відповідальність центробанків: теоретичні засади та інституціональні дилеми. Стверджується, що посткризова тенденція до посилення макрофінансової відповідальності центробанків має бути пов’язана не стільки з активістським управлінням попитом, скільки з переглядом погляду на зв’язки між реальним і фінансовим сектором. Констатується, що відмінності в баченні взаємодії цінової та фінансової стабільності і, відповідно, інституціональної модальності їх забезпечення ускладнюють пошук оптимального інституціонального дизайну центробанку з розширеною зоною відповідальності. Обґрунтовано, що підвищення відповідальності за фінансову стабільність має відбуватись на основі збереження пріоритетності мандату цінової стабільності, підвищення рівня незалежності центробанку та координації між монетарною і макропруденційною політикою. Показано, що вразливість макрофінансової відповідальності до політичного тиску тільки підвищується, а тому політична незалежність повинна забезпечити захист компетенцій центробанку одразу у сфері цінової та фінансової стабільності. Козюк В. В. Макрофинансовая ответственность центробанков: теоретические основы и институциональные дилеммы. Утверждается, что посткризисная тенденция к усилению макрофинансовой ответственности центробанков должна связываться не столько с активистским управлением спросом, сколько с пересмотром взгляда на связи между реальным и финансовым сектором. Констатируется, что различия в видении взаимодействия ценовой и финансовой стабильности и, соответственно, институциональной модальности их обеспечения затрудняют поиск оптимального институционального дизайна центробанка с расширенной зоной ответственности. Доказано, что повышение ответственности за финансовую стабильность должна происходить на основе сохранения приоритетности мандата ценовой стабильности, повышения уровня независимости центробанка и координации между монетарной и макропру- денциальной политикой. Показано, что уязвимость макрофинансовой ответственности к политическому давлению только повышается, а потому политическая независимость должна обеспечить защиту компетенций центробанка одновременно в сфере ценовой и финансовой стабильности. Kozjuk V. Macrofinancial responsibility of central banks: theoretical foundations and institutional dilemmas. Introduction. Postcrisis tendency to enhance central bank’s macrofinancial responsibility should be related to real-financial inter-linkages rethinking but not to activistic demand management. Different approaches on how price stability and financial stability are inter-related, as well, as different institutional modalities of how to achieve them are making more complicate optimal institutional design of central bank with increased zone of responsibility.Purpose. Taking into account different macroeconomic viewpoints on the role of financial instability in macroeconomic fluctuations and institutional challenges for central bank independence the purpose of the paper is to validate that enhanced macrofinancial responsibility of central banks should be balanced by additional measures in direction to facilitate autonomous regulatory status.Results. Different views on how to enhance macroeconomic stability and what the role of central banks in new macrofinancial environment provide serious challenge for optimal designing of central bank’s macrofinancial responsibility. The problem not only relate to how price and financial stability are inter-related but also to how define the wrong way policy then price and financial stability are in non-linear relations. The difficulties in this segment may affect far reaching political consequences while assessing central bank from political economy point of view. Also it is necessary to take into account that macroprudential toolkit may overlap with monetary policy instruments providing additional regulatory distortions. Clear institutialisation of relations between price and financial stability responsibilities will help to avoid political economy type of manipulations with central bank new tasks. Priority of price stability should be kept while financial stability mandate should be clarified and tied to macroprudential regulation. In the same time more active central bank’s participance in the post-crisis economy should be based not on standard Keynesian activism but on enhanced financial responsibility balanced with protection of central bank independence in new regulatory areas.Conclusions. It the article it is stressed that enhanced macrofinancial responsibility should be based on unchanged priority of price stability mandate, increased level of central bank independence and coordination between monetary and macroprudential policies. It is shown that vulnerability of macrofinancial responsibilities to political pressure is going to increase. Political independence of central banks should protect them in the area of price stability and financial stability all together.